Why the Finger? - Williams, David T. (2003)
Explains a verse from the "Bible" regarding the indication that Jesus Christ cast out demons by the finger of God, which the parallel in the gospel of Matthew refers to the Spirit. Restriction of the work of the Spirit to prophecy; Application of the finger as a picture for the Spirit; Use of the hand for the action of God.
Keywords: Bible; Demonology; FINGERS; God; Prophecy